On the cultivation of tobacco in Ireland - Walker, John A. (Statistical and Social Inquiry Society of Ireland, 1885)
Some years ago the cultivation of tobacco in Ireland was advocated in the press and in parliament, and the question: What was the hindrance to the cultivation of the plant in this country? was put to the Chancellor of the Exchequer, who at the time replied, I believe, that the main objection arose from the difficulty of collecting the tax upon it. Were this the only obstacle in the way, it could be overcome as in France, Germany, and elsewhere has been the case; but it is thought there are other grounds of objection?partly fiscal and partly climatic?which appear to stand in the way of the profitable cultivation of tobacco in these kingdoms.
Read before the Society, 20 January 1885
Keywords: Irish agriculture; Tobacco cultivation; Land use; Economic growth; 314.15